Human papillomavirus in conjunctival papilloma. Issue 7 (1st July 2001) - Sjö, Nicolai Christian; Heegaard, Steffen; Prause, Jan Ulrik; von Buchwald, Christian; Lindeberg, Henning
Abstract : AIM: To examine conjunctival papillomas for the presence of human papillomavirus (HPV) and koilocytosis. METHODS: Archival paraffin embedded tissue from 55 conjunctival papillomas was analysed for the presence of HPV by polymerase chain reaction and subsequent filter hybridisation. Histological sections of the 55 papillomas were evaluated for the presence of koilocytosis. RESULTS: HPV was present in 48 of 52 (92%) β globin positive papillomas. HPV type 6/11 were found in 40 of 47 investigated papillomas and a double infection with HPV 6/11 and 16 was identified in a single papilloma. In six papillomas the HPV type could not be identified. Koilocytosis was present in 22 of 55 papillomas (40%). CONCLUSION: There is a strong association between HPV and conjunctival papillomas. HPV type 6/11 is the most common HPV type in conjunctival papilloma. The sensitivity of koilocytosis as an indicator of HPV in conjunctival papilloma is low.